2023
DOI: 10.1021/acs.jcim.3c01429
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT in Drug Discovery: A Case Study on Anticocaine Addiction Drug Development with Chatbots

Rui Wang,
Hongsong Feng,
Guo-Wei Wei

Abstract: The birth of ChatGPT, a cutting-edge language model-based chatbot developed by OpenAI, ushered in a new era in AI. However, due to potential pitfalls, its role in rigorous scientific research is not clear yet. This paper vividly showcases its innovative application within the field of drug discovery. Focused specifically on developing anticocaine addiction drugs, the study employs GPT-4 as a virtual guide, offering strategic and methodological insights to researchers working on generative models for drug candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Chatbots function as facilitators, guiding researchers toward innovative approaches and productive pathways to develop successful drug candidates. Additionally, the study illuminates the collaborative synergy between human expertise and AI support, demonstrating how ChatGPT’s cognitive abilities enhance the design and advancement of pharmaceutical solutions . ChatGPT exhibits lots of innovative applications in material science such as Materials discovery: ChatGPT can aid in the design of new materials with desired properties.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chatbots function as facilitators, guiding researchers toward innovative approaches and productive pathways to develop successful drug candidates. Additionally, the study illuminates the collaborative synergy between human expertise and AI support, demonstrating how ChatGPT’s cognitive abilities enhance the design and advancement of pharmaceutical solutions . ChatGPT exhibits lots of innovative applications in material science such as Materials discovery: ChatGPT can aid in the design of new materials with desired properties.…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, the study illuminates the collaborative synergy between human expertise and AI support, demonstrating how ChatGPT's cognitive abilities enhance the design and advancement of pharmaceutical solutions. 46 ChatGPT exhibits lots of innovative applications in material science such as…”
Section: ■ Introductionmentioning
confidence: 99%
“…More recently, generative AI language models, particularly Chat Generative Pre-trained Transformer (ChatGPT) [19][20][21], have garnered substantial interest with applications including performance of autonomous research [22], drug discovery [23][24][25], bioinformatic analysis [26,27], the potential to aid in clinical diagnosis [28,29], among others [30][31][32]. Unlike AlphaFold2, RoseTTAFold, and protein language models, ChatGPT is trained on natural language datasets and its neural network architecture is tailored towards understanding and generating natural language text rather than structural modelling.…”
Section: Introductionmentioning
confidence: 99%
“…The terms AI and ChatGPT have grown more and more synonymous over the past year. There are various applications of AI bots in journalism and media education, 1 scientific applications like peer reviews, 2 drug discovery, 3 material design, 4 or even scientific discovery itself. 5 In education, initial research on using generative AI mainly revolved around strengths and weaknesses 6 and opportunities and challenges.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The terms AI and ChatGPT have grown more and more synonymous over the past year. There are various applications of AI bots in journalism and media education, scientific applications like peer reviews, drug discovery, material design, or even scientific discovery itself . In education, initial research on using generative AI mainly revolved around strengths and weaknesses and opportunities and challenges. , Scholars extensively tested what potential ChatGPT has in the educational context by evaluating answers given by the generative AI and proposed a range of applications in several fields of education. This same development was seen in chemistry education, where scientists evaluated academic answers given by AI, describing mixed performances by ChatGPT in terms of application of knowledge. , They compared AI-generated answers to student answers and found that the AI was sound in some areas but made mathematical mistakes that students would not make .…”
Section: Introductionmentioning
confidence: 99%